Sustainable well-being: An empirical exploration on human interdependence with other humans - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor; Abdullah, Alias (2016)
This study is a part of ongoing research to discover subjective measures of sustainable well-being manifested in (i) Human Interdependence with other Humans (HIH) and (ii) Human Interdependence with the Environment (HIE). This paper focuses on HIH. ISSUES: An increasing number of subjective well-being studies discovered that sustainable well-being is a product of human interdependency. However, a conclusive empirical study on components and indicators that determine the human interdependency is in need. AIM: This study intends to provide empirical evidence on the components that constitute HIH. METHOD: Questionnaire Survey and Principal Component Analysis (PCA) were implemented to determine the components of HIH. Before the Questionnaires, the research had already theoretically explored four separate dimensions to HIH. The dimensions of HI were (i) personal empowerment, (ii) positive relationships, (iii) organisational opportunity and (iv) community mobilisation. Potential and measurable HIH indicators were discovered through literature review and converted into 40 self-reported items. Survey Questionnaires were conducted in central regions of Malaysia inquiring respondents of their levels of HIH. FINDINGS: There were 12 components extracted in total, based on four separate PCA analysis for each HIH dimension. LIMITATION: Full reliance on literature review and PCA in discovering the components for HIH is the constraint of the research. An in-depth qualitative approach such as semi-structured interviews could potentially identify other possible determinants to HIH. SIGNIFICANCE: This study distinguishes the determinants of HIH. The empirical evidence of HIH at the local scale contributes to the practicality of measuring sustainable well-being through HIH.